2015
DOI: 10.1016/j.jad.2015.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Switching methods of self-harm at repeat episodes: Findings from a multicentre cohort study

Abstract: BackgroundSelf-poisoning and self-injury have widely differing incidences in hospitals and in the community, which has led to confusion about the concept of self-harm. Categorising self-harm simply by method may be clinically misleading because many hospital-attending patients switch from one method of harm to another on subsequent episodes. The study set out to determine the frequency, pattern, determinants and characteristics of method-switching in self-harm episodes presenting to the general hospital. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 13 publications
6
39
0
2
Order By: Relevance
“…The proportions of people that we allocated to our four categories of self-harm method are similar to those we reported previously together with data from Manchester and Oxford (Lilley et al, 2008). In particular, the proportion of people who had self-harmed using combined methods is in keeping with that seen in multicentre monitoring (Lilley et al, 2008;Owens et al, 2015).…”
Section: Characteristics Of the Study Samplesupporting
confidence: 78%
See 2 more Smart Citations
“…The proportions of people that we allocated to our four categories of self-harm method are similar to those we reported previously together with data from Manchester and Oxford (Lilley et al, 2008). In particular, the proportion of people who had self-harmed using combined methods is in keeping with that seen in multicentre monitoring (Lilley et al, 2008;Owens et al, 2015).…”
Section: Characteristics Of the Study Samplesupporting
confidence: 78%
“…Two acts (say self-poisoning followed by self-injury) will be classified as rapid repetition if each leads to a separate hospital attendance but as one combined episode if they occurred very rapidly and presentation was deferred until after the second act. Since repetition very often involves a change of method (Owens et al, 2015) it is not implausible that this overlap between the definitions of the two presentations is matched by some more general overlap between the phenomena (use of more than one method, early repetition), which may account in part for their similar outcomes.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the sample size may, in part, be a product of the definition of 'recent' employed. Research evidence suggests that, if repeated, there is often a very short time period between self-harm episodes (Owens et al, 2015). Therefore, it could be suggested that the 3 month timeframe increases the probability of capturing enactment.…”
Section: Coping Self-harm Ideation and Enactment 18mentioning
confidence: 99%
“…However, recent cohort analysis indicates that many individuals switch self-harm methods in subsequent episodes, and so division of participants by methods alone for prediction of repetition may not be appropriate (Owens et al, 2015).…”
Section: Strengths and Limitations Of This Systematic Reviewmentioning
confidence: 99%